TATA KELOLA DATABASE PERGURUAN TINGGI YANG OPTIMAL DENGAN DATA WAREHOUSE - Spits Warnars (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2010)
The emergence of new higher education institutions has created the competition in higher education market, and data warehouse can be used as an effective technology tools for increasing competitiveness in the higher education market. Data warehouse produce reliable reports for the institution’s high-level management in short time for faster and better decision making, not only on increasing the admission number of students, but also on the possibility to find extraordinary, unconventional funds for the institution. Efficiency comparison was based on length and amount of processed records, total processed byte, amount of processed tables, time to run query and produced record on OLTP database and data warehouse. Efficiency percentages was measured by the formula for percentage increasing and the average efficiency percentage of 461.801,04% shows that using data warehouse is more powerful and efficient rather than using OLTP database. Data warehouse was modeled based on hypercube which is created by limited high demand reports which usually used by high level management. In every table of fact and dimension fields will be inserted which represent the loading constructive merge where the ETL (Extraction, Transformation and Loading) process is run based on the old and new files.